Clinical manifestations and imaging and pathological features of giant cell angioblastoma: Report of four cases and literature review - Li, Qingbin; Zhang, Zhaohua; Chen, Guocai; Hu, Yongbo; Mao, Rongjun; Xie, Le; Chen, Shaoluan; Lao, Yongqiang; Gao, Junqing (Frontiers in Surgery, 2023)
Giant cell angioblastoma is a relatively rare vasogenic tumour. To date, studies on its clinical manifestations, imaging characteristics, pathological features, and prognosis are extremely limited and unknown, with only a few cases recorded. In this study, four cases of giant cell angioblastoma confirmed by pathological examination were reported to improve our understanding and deep exploration of the tumour spectrum. All cases in our study were male, including two adults and two boys. The lesions were located in the lower segment of the femur, medial condyle of the femur, knee joint, and popliteal fossa. Regarding the imaging characteristics, two patients with lesions in bone showed bone destruction, while the other two had lesions that invaded soft tissues, showing irregular, abnormal signal shadows and obvious enhancement. Histopathological analysis revealed that the nodular tumour tissue was mainly composed of oval and spindle cells, with varying numbers of osteoclast-like multinucleated giant cells, and the interstitial tissues were often filled with blood vessels of different sizes. The immunophenotype demonstrates that endothelial cells of small vessels in nodules expressed CD31, SMA, and ERG, while osteoclast-like multinucleated giant cells and histiocytes expressed CD68 and CD163, and the surrounding cells expressed SMA. All four patients were treated with surgical resection. One of them relapsed 1 month after surgery and received a second surgical resection. No distant metastasis or death occurred during the follow-up period. This study indicates that giant cell angioblastoma is a local invasive vascular tumour that can develop both in children and adults with skin, mucous membrane, soft tissue, and bone involvement. Imaging characteristics show bone destruction and irregular, abnormal signal shadows; in addition, obvious pathological morphological features can be observed. Currently, the treatment is mainly surgical resection, and interferons may be used as adjuvant chemotherapy.